Penerapan Kontruksi Ekologis dalam Pembelajaran Bahasa dan Sastra Indonesia pada Siswa di MA Ummul Quro Putri Pamekasan - Hesty Kusumawati; Mochamad Arifin Alatas (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The application of ecological construction in Indonesian language and literature learning is a significant effort to integrate environmental awareness into the educational process. This study aims to explore how ecological construction is applied in language and literature learning at MA Ummul Quro Putri Pamekasan using a descriptive qualitative method and a naturalistic approach. Data were collected through observations, semi-structured interviews, and documentation, involving teachers, students, and school principals as primary data sources. Based on the theory of ecological construction, which emphasizes the reciprocal relationship between humans, the environment, and culture, the study found that ecological construction was implemented by integrating environmental themes into learning materials, using teaching resources relevant to ecological issues, and engaging students in discussions that connect literature with environmental awareness. Teachers act as facilitators, encouraging students to relate learning to the ecological realities around them. Furthermore, ecological construction-based learning effectively enhances students' critical thinking, imagination, creativity, and instills sustainability values. The study concludes that implementing ecological construction positively impacts students' understanding of the importance of maintaining a balance between humans, nature, and culture, contributing to the development of holistic, sustainability-oriented learning approaches.